2018
DOI: 10.1029/2018jd028584
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Potential of Using Satellite‐Based Precipitation Radars as Reference for Evaluating Multisatellite Merged Products

Abstract: This work investigates the viability of using the Global Precipitation Mission (GPM) Dual‐frequency Precipitation Radar (DPR) as a reference for evaluating multisatellite precipitation products in locations where a ground‐based reference is not available. The Integrated Multi‐Satellite Retrievals for Global Precipitation Measurement (IMERG) version V05 products (early, late, and final) and the microwave‐only (MW) and infrared‐only (IR) components are evaluated against two reference data sets, derived from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 60 publications
(75 reference statements)
0
7
0
Order By: Relevance
“…TCA clearly confirms that 3DPRD performs consistently better than OceanRAIN, as also shown by the continuous error metrics. Khan et al [48] demonstrated that IR estimates are affected by the largest systematic and random errors over land compared to the other IMERG products and components and their improvement could be critical to enhance the merged products. The findings over ocean also point to larger errors in IR estimates over oceans, thus providing an opportunity to improve the merged products also over oceans.…”
Section: Discussionmentioning
confidence: 99%
“…TCA clearly confirms that 3DPRD performs consistently better than OceanRAIN, as also shown by the continuous error metrics. Khan et al [48] demonstrated that IR estimates are affected by the largest systematic and random errors over land compared to the other IMERG products and components and their improvement could be critical to enhance the merged products. The findings over ocean also point to larger errors in IR estimates over oceans, thus providing an opportunity to improve the merged products also over oceans.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the Tropical Rainfall Measurement Mission precipitation radar, the DPR is more capable of sensing light rain and snowfall. Verification results showed that GPM DPR products can serve as a reliable reference for the calibration of multisatellite 10.1029/2019GL086207 precipitation products (Khan et al, 2018). The product we used in our study was Level 2 DPR Ka&Ku single orbit rainfall estimates (2A-DPR), with a spatial resolution of 5.2 km × 125 m and temporal resolution of 16 orbits per day.…”
Section: Methodsmentioning
confidence: 99%
“…They found that the correlation between the satellite and radar data was generally high; however, it decreased significantly over the storm core. Further studies have compared satellite precipitation retrievals with ground radar estimates (Beck et al 2019;Chen et al 2020;ElSaadani et al 2018;Furl et al 2018;Gebregiorgis et al 2018;Khan et al 2018;Prat and Nelson 2015;Rios Gaona et al 2017;J. Zhang et al 2018;X.…”
Section: Introductionmentioning
confidence: 99%